2016
DOI: 10.5469/neuroint.2016.11.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Pipeline Embolization Device for Large/Giant or Fusiform Aneurysms: An Initial Multi-Center Experience in Korea

Abstract: PurposeThe purpose of this study was to assess the safety and early outcomes of the Pipeline device for large/giant or fusiform aneurysms.Materials and MethodsThe Pipeline was implanted in a total of 45 patients (mean age, 58 years; M:F=10:35) with 47 large/giant or fusiform aneurysms. We retrospectively evaluated the characteristics of the treated aneurysms, the periprocedural events, morbidity and mortality, and the early outcomes after Pipeline implantation.ResultsThe aneurysms were located in the internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 23 publications
3
15
0
1
Order By: Relevance
“…This highlights the efficacy of the PED that resulted in a rate of aneurysm occlusion of 81.5% after a 5-year experience with the device. This rate is consistent with those reported in other studies in the literature that have shown a high complete aneurysm occlusion rate, with most studies reporting occlusion rates > 80%, 11,16 which compares favorably to that of endovascular coil embolization, where the reported complete occlusion rate is 66% (ISAT; International Subarachnoid Aneurysm Trial). 23 None of the aneurysms with complete occlusion or near-complete occlusion recurred during follow-up.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This highlights the efficacy of the PED that resulted in a rate of aneurysm occlusion of 81.5% after a 5-year experience with the device. This rate is consistent with those reported in other studies in the literature that have shown a high complete aneurysm occlusion rate, with most studies reporting occlusion rates > 80%, 11,16 which compares favorably to that of endovascular coil embolization, where the reported complete occlusion rate is 66% (ISAT; International Subarachnoid Aneurysm Trial). 23 None of the aneurysms with complete occlusion or near-complete occlusion recurred during follow-up.…”
Section: Discussionsupporting
confidence: 89%
“…Good clinical outcomes have been reported with flow diversion of saccular or nonsymptomatic fusiform posterior circulation aneurysms. 16 Acceptable morbidity and mortality rates (0%-9.4%) and high efficacy have been shown in these aneurysms, 85.2% in this study, comparable to anterior circulation aneurysms. Treatment with the PED may be a preferable alternative to open surgical treatment for these aneurysms.…”
Section: Aneurysm Locationsupporting
confidence: 62%
See 1 more Smart Citation
“…Their series reported minor complications in 7.6% (4.2% transient J Korean Neurosurg Soc 63 (2) : 137-152 ischemic attacks; 3.4% minor stroke) and major complications in 1.6% (0.8% major stroke; 0.8% mortality 23) . In a similar study, Kim et al 60) reported 77.4% complete occlusion rate at 2-years for large/giant (>15 mm) intracranial aneurysms undergoing FDS placement. They reported a 4.4% procedural morbidity rate and no mortality.…”
Section: Wide-necked Large and Giant Aneurysmsmentioning
confidence: 77%
“…However, this involves repeat craniotomy and delays tumor surgery, more than the preoperative coiling strategy. Endovascular treatment of UIA is very safe and effective even in wide neck and large aneurysms (20212223). Thus, cUIA coiling and subsequent tumor surgery is an alternative option.…”
Section: Discussionmentioning
confidence: 99%